2007
DOI: 10.1016/j.chembiol.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

A Phenotypic Small-Molecule Screen Identifies an Orphan Ligand-Receptor Pair that Regulates Neural Stem Cell Differentiation

Abstract: High-throughput identification of small molecules that selectively modulate molecular, cellular, or systems-level properties of the mammalian brain is a significant challenge. Here we report the chemical genetic identification of the orphan ligand phosphoserine (P-Ser) as an enhancer of neurogenesis. P-Ser inhibits neural stem cell/progenitor proliferation and self-renewal, enhances neurogenic fate commitment, and improves neuronal survival. We further demonstrate that the effects of P-Ser are mediated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 54 publications
(59 reference statements)
0
55
0
Order By: Relevance
“…As a result, several steroids that promoted hES cell differentiation were identified, and the antihypertensive drug pinacidil was shown to affect hES cell survival. Phenotypic screens can be advantageous because they can be carried out in cells by examining multiple markers and functional changes (for example, cell morphology and behavior) using automated high-content imaging technologies in a high-throughput manner [1,4,36,37] .…”
Section: High-throughput/content Screening (Primary Screen)mentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, several steroids that promoted hES cell differentiation were identified, and the antihypertensive drug pinacidil was shown to affect hES cell survival. Phenotypic screens can be advantageous because they can be carried out in cells by examining multiple markers and functional changes (for example, cell morphology and behavior) using automated high-content imaging technologies in a high-throughput manner [1,4,36,37] .…”
Section: High-throughput/content Screening (Primary Screen)mentioning
confidence: 99%
“…One study reported that phosphoserine (P-Ser) increased neurogenesis in hES cellderived neural progenitors [1] . It also confirmed that the effects of P-Ser are mediated by the group III metabotropic glutamate receptor 4 (mGluR4).…”
Section: A Series Of Secondary Assaysmentioning
confidence: 99%
See 3 more Smart Citations